2003
DOI: 10.1039/b300439b
|View full text |Cite
|
Sign up to set email alerts
|

Covalent immobilization of oligonucleotides on p-aminophenyl-modified carbon screen-printed electrodes for viral DNA sensing

Abstract: DNA-sensing platforms were prepared by covalently attaching oligonucleotide capture probes onto p-aminophenyl-functionalized carbon surfaces and applied to the determination of an amplified herpes virus DNA sequence in an electrochemical hybridization assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 13 publications
0
45
0
Order By: Relevance
“…(Kuralay et al, ; Miodek et al, ) Electrochemical biosensors applying DNA probes covalently attached to carbon electrodes have been described with prolonged storage stability. (Mazloum‐Ardakani et al, ; Ruffien et al, ) A differential pulse voltammetry biosensor with DNA probes covalently bound to glassy carbon electrodes, for example, showed no loss of sensitivity after 10 days storage in buffer at 4 °C. (Amouzadeh Tabrizi and Shamsipur, ) Ulianas et al reported a storage stability of 45 days for an electrochemical biosensor with amino‐modified DNA probes covalently attached to succinimide groups of acrylic microspheres when stored in phosphate buffer at 4 °C.…”
Section: Resultsmentioning
confidence: 99%
“…(Kuralay et al, ; Miodek et al, ) Electrochemical biosensors applying DNA probes covalently attached to carbon electrodes have been described with prolonged storage stability. (Mazloum‐Ardakani et al, ; Ruffien et al, ) A differential pulse voltammetry biosensor with DNA probes covalently bound to glassy carbon electrodes, for example, showed no loss of sensitivity after 10 days storage in buffer at 4 °C. (Amouzadeh Tabrizi and Shamsipur, ) Ulianas et al reported a storage stability of 45 days for an electrochemical biosensor with amino‐modified DNA probes covalently attached to succinimide groups of acrylic microspheres when stored in phosphate buffer at 4 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Discrimination of dopamine over ascorbic acid (Downard et al, 1995), limitation of nonspecific protein adsorption (Downard and Bin Mohamed, 1999), and applications towards corrosion resistance (Chausse et al, 2002) have been reported. The immobilization of biomolecules such as glucose oxidase (Bourdillon et al, 1992), DNA (Shabani et al, 2006), alkaline phosphatase (Ruffien et al, 2003), and horseradish peroxidase (Liu and Gooding, 2006), have also been demonstrated. Diazonium chemistry has also been shown to be suitable for the electrically addressable biomolecular functionalization of single-walled carbon nanotubes and vertically aligned carbon fiber electrodes for DNA detection (Lee et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, some authors have reported the modification of glassy carbon surfaces by means of electrochemical methods using 4-phenylacetic acid diazonium salt to produce stable and reproducible enzymatic films [13] and also for the selective determination of DA cation in the presence of ascorbate at physiological pH [9]. The electrochemically assisted method has been used to attach modifiers to carbon materials ranging from glassy carbon (GC) and highly ordered pyrolytic graphite (HOPG) [1,14] to carbon fibers [15], felt [17] and powder [18] to screen-printed carbon films [19,20] and pyrolyzed photoresist films (PPFs) [21][22][23] and common metals such as steel [24], zinc [25,26], etc. At least five factors come out to significantly influence the structure of films formed on carbon substrates by electroreduction of aryl diazoniums.…”
Section: Introductionmentioning
confidence: 99%